Relationship Marketing in Service Organizations: A Review of the Dynamics of Agency-client Relationships - Ogbemudia, Sarah (2006)
Ongoing relationships between businesses and their customers are receiving renewed interest in marketing as increasing number of firms are shifting their attention from transactional to relationship marketing (Sheth and Parvatiyar 1995). Companies are increasingly realising the importance of customer loyalty and at such prioritising customer retention. Their attention is now focused on retaining satisfied customers, as the costs of acquiring new customers largely outweigh that of retaining existing ones. Developing and maintaining a loyal customer base is viewed as the single most important driver of long-term financial performance (Reichheld and Sasser, 1990). As a result relationship building also sometimes referred to as relationship marketing has become a new area of research for authors. The building of strong customer relationships has been recognised as a means for gaining a competitive advantage (Reichheld 1993). For service businesses, strong customer relationship is particularly important because of the high level of interpersonal contact which constitutes the main source of evaluating service quality as there is relatively a lack of objective measures for service evaluation. This report critically reviews the relevance of relationship marketing in a service organization with particular emphasis on agency-client relationships which ties in with Jupiter's nature of business. The aim is to evaluate relationship marketing techniques obtained from relevant literature and to contrast these with the relationship management strategies in Jupiter. The report concludes with recommendations on ways to enhance relationship building skills.